Performance analysis of a lever piezoelectric energy harvester for roadway applications. (December 2021) - Ding, Guangya; Luo, Hongjun; Wang, Jun; Yuan, Guohui
A novel lever piezoelectric energy harvester (LPEH) was designed for installation in an actual roadway for energy harvesting. The model incorporates a lever module that amplifies the applied traffic load and transmits it to the piezoelectric ceramic. To observe the piezoelectric growth benefits of the optimized LPEH structure, the output characteristics and durability of two energy harvesters, the LPEH and a piezoelectric energy harvester (PEH) without a lever, were measured and compared by carrying out piezoelectric performance tests and traffic model experiments. Under the same loading condition, the open circuit voltages of the LPEH and PEH were 20.6 and 11.7 V, respectively, which represents a 76% voltage increase for the LPEH compared to the PEH. The output power of the LPEH was 21.51 mW at the optimal load, which was three times higher than that of the PEH (7.45 mW). The output power was linearly dependent on frequency and load, implying the potential application of the module as a self-powered speed sensor. When tested during 300, 000 loading cycles, the LPEH still exhibited stable structural performance and durability.